Bilaterale Verletzung der A. thoracica interna nach stumpfem Thoraxtrauma - Jungbluth, Pascal; Grassmann, J. -P.; Fuerst, G.; Windolf, J.; Wild, M.; Betsch, Marcel (Unfallchirurg, 2010)
Injuries of the internal mammary artery after blunt thoracic trauma are rare but potentially fatal. A specific characteristic of these injuries is that they can become symptomatic even after a delay of several weeks. This article reports on the diagnosis and treatment of a 41-year-old motorcycle rider who suffered bilateral injuries of the internal mammary artery after a motorcycle accident without any additional bony lesions. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Angiography; Arterial vascular injury; Blunt chest trauma